Magnetic Resonance Imaging Quantification of the Liver Iron Burden and Volume Changes Following Treatment With Thalidomide in Patients With Transfusion-Dependent ß-Thalassemia - Che, Jinlian; Luo, Tianying; Huang, Lan; Lu, Qiyang; Yan, Da; Meng, Yinying; Xie, Jinlan; Chen, Weihua; Chen, Jiangming; Long, Liling (Frontiers in Pharmacology, 2022)
Clinical trials have indicated that thalidomide could be used to treat thalassemia, but evidence of changes in liver iron burden and liver volume during thalidomide treatment is lacking. This study aimed to evaluate the liver iron burden and volume changes following thalidomide treatment in patients with transfusion-dependent β-thalassemia. A total of 66 participants with transfusion-dependent β-thalassemia were included in this prospective cohort study between January 2017 and December 2020. Patients were treated with thalidomide (150–200 mg/day) plus conventional therapy. Liver volume, liver R2*, and hepatic muscle signal ratio (SIR)_T1 and SIR_T2 were measured with magnetic resonance imaging (MRI), and serum ferritin, hemoglobin, erythrocyte and platelet counts, and liver function were measured at baseline and at the 3rd and 12th months. Adverse events were also noted. Patients showed progressive increase in hemoglobin, erythrocyte, platelet count, SIR_T1, and SIR_T2 during the 12-month follow up. Serum ferritin, R2*, and liver volume progressively decreased during the follow up. The R2* value had a significantly positive correlation with serum ferritin, and SIR_T1 and SIR_T2 had a significantly negative correlation with serum ferritin. No serious adverse events were observed. This study showed that thalidomide could potentially be used to successfully treat patients with transfusion-dependent β-thalassemia; the liver iron burden and liver volume could be relieved during treatment, and the MRI-measured R2*, SIR_T1, and SIR_T2 may be used to noninvasively monitor liver iron concentration.